Pelaksanaan Posyandu Balita Door to Door di Kelurahan Pedalangan Kota Semarang - Hany Putri Antari; Intan Zainafree (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The COVID-19 pandemic caused posyandu activities for toddlers to be temporarily suspended and began to be carried out again in August 2020 with a door to door system. This study aims to determine the achievements of posyandu toddlers door to door in the Pedalangan Village area with program evaluation. This study used descriptive qualitative. Determination of informants using purposive sampling technique. The main informants are the head of the puskesmas, the person in charge of the program, nutritionists, cadres and mothers of toddlers. data collection by means of observation, documentation and in-depth interviews to 8 people. Data validity using triangulation techniques to 4 people. The resukts are in the evaluation of input points, there are differences in facilities during the pandemic and before the pandemic. In the process, posyandu for toddlers during the pandemic was carried out door to door, while before the pandemic it was carried out directly. At the output point, there was an increase in D/S in 2021 of 86.4% compared to 2020, which was 57.4%. the conclusion is toddler posyandu activities before the pandemic are different from after the pandemic. D/S coverage in 2021 of 86.4% is in accordance with the target of Indonesia Sehat.